Effect of Sex Differences in Sports Groups on Hamstring Flexibility Based on the Sitreach Test: New Parameters for Chilean Athletes - Aedo-Munoz, E (Editura Universitatii din Pitesti, 2019)
Although the SR test does not satisfactorily measure lower back flexibility and is only a moderately valid measure of hamstring flexibility, it is still the only field test that is practical and easy to administer. Therefore, the aims of the study were: i) to find optimum values which would characterize the SR test for different sports; ii) to evaluate changes in SR test parameters to measure the hamstring flexibility for specific sport groups; and iii) to indicate gender-related differences in different sport groups. The sample was composed for 424 athletes, 181 male and 243 female separated in water sports (n=45), artistic performance sports (n=75), track and field (n=113), target sports (n=10), team sports (n=98), combat sports (n=35) and radical sports (n=48).All them performed the sit and reach test in three trials. Regression analysis and a two-way ANOVA followed by Bonferroni post hoc were used, p ≤.05. Results demonstrated significand differences between female vs. male athletes in artistic performance sports (53.5±6.2cm vs. 48.2±8.9cm), team sports (46.3±6.7cm vs. 40.9±7.7cm), combats (48.3±10cm vs. 39.9±8.2cm) and radical sports (53.5±6.6cm vs. 48.0±8.1cm); artistic performance sport and radical sports groups presented higher values of SR than track and field, target sports and team sports. Regression analysis demonstrated sex dependence in SR values of radical, combat, artistic and team sports. In conclusion, female and male Chilean athletes achieved above-average results by the standards of the sit-andreach test for all sport group, finding new optimum values for this respective group. © JPES.